Pelatihan Copywriting untuk Optimalisasi Pemasaran Digital Kepada SMK Bakti Nusantara 666 Kabupaten Bandung - Wazdi, Adi Indradi; Aisya Aprilia, Gadis (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2022)
One of the standard of a successful digital marketing campaign, is being able to maximize product and service promotion techniques using digital distribution channels such as; websites, Adwords, email or various other social network platforms. One of the ideal requirement of SMK graduates is able to succeed in the business world, therefore they must be equipped with good marketing skills. Seeing the importance of a marketer having Copywriting skills, Copywriting training is needed for them. The method used is the ABCD approach where the "assets" itself are the students of SMK Bakti Nusantara 666 whom have their own start up business. The training is carried out in the form of giving a basic marketing knowledge and giving them a set of training in how to write an attractive ad script and creating article’s titles by using a set of keywords, which had a high ranking in the Google search engine. The training itself was done in two days at school and Ma’soem University Language Center Laboratorium. From the said training, it could be concluded that, indeed, there is an increase in language skills and copywriting of each participant. And the average skill mastered by participants was writing CTA.